1977
DOI: 10.1007/bf01569293
|View full text |Cite
|
Sign up to set email alerts
|

Blur: A sufficient accommodative stimulus

Abstract: Experiments under a variety of open and closed loop feedback configurations demonstrate that accommodative responses to target blur are equivalent to those to defocus blur; this supports blur as the 'sufficient' neurological stimulus to accommodations. The hunting action of accommodation compensates for the even error aspect of blur and also adaptively minimizes any close loop error components while finally accepting open loop components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…47 Cortical-like sensitivity to interocular disparity is certainly present in pupillary responses. 48 Although longitudinal chromatic aberration seems to be a major driver of the sign accommodation 49 luminance blur alone is a sufficient accommodative cue, 50 and the effects of longitudinal chromatic aberration are thought to be governed by both color and luminance channels. 51 Certainly extrastriate cortical areas producing pupil constriction in the macaque also produce accommodation and convergent eye movements.…”
Section: Discussionmentioning
confidence: 99%
“…47 Cortical-like sensitivity to interocular disparity is certainly present in pupillary responses. 48 Although longitudinal chromatic aberration seems to be a major driver of the sign accommodation 49 luminance blur alone is a sufficient accommodative cue, 50 and the effects of longitudinal chromatic aberration are thought to be governed by both color and luminance channels. 51 Certainly extrastriate cortical areas producing pupil constriction in the macaque also produce accommodation and convergent eye movements.…”
Section: Discussionmentioning
confidence: 99%
“…The retinotopic system then acts as the fine-focus control, continually monitoring and responding very finely to small alterations in retinal image contrast. 1,2 Blur is regarded as the primary drive of the accommodation system. It has been demonstrated that blur is a sufficient stimulus to accommodation alone and that the system can still produce adequate responses, even when other cues are eliminated.…”
mentioning
confidence: 99%
“…23 This experiment aims to determine whether adaptation to defocus influences the closed-loop negative feedback blur detection system of the dynamic accommodation mechanism, which is highly dependent on blur feedback. 7 The effect of adaptation to defocus on the accommodation latency and response times to step and sinusoidal target vergence changes were investigated. Because of the differential refractive effect of blur adaptation and accommodation output, 12 the accommodation response was studied in a group of EMMs, EOMs, and LOMs.…”
Section: Figurementioning
confidence: 99%